Cold Flow Simulation of a 30 kW(th) CFB Riser with CPFD - YILMAZ, BARIŞ; ÖZDOĞAN, ZEYNEP SİBEL (ISFAHAN UNIV TECHNOLOGY, 2020)
A 30 kW(th) Circulating fluidized bed (CFB) combustor is experimentally and numerically investigated under cold flow conditions. Barracuda software based on Computational Particle Fluid Dynamics (CPFD) method is utilized for simulations. The influences of bed inventory and drag model on flow hydrodynamics were investigated considering pressure and velocity profiles and particle concentration. Two advanced drag models, namely Energy minimization multi-scale (EMMS) and Wen-Yu/Ergun were selected for this study. The simulations were performed with initial bed material masses of 3.79, 4.55 and 5.20 kg corresponding to 2.5, 3 and 3.5 diameters height of riser, respectively. With increasing bed inventory pressure drops and solid concentration increase. The axial particle velocities slightly change with bed inventory. The comparison of simulation results with experimental measurements was resulted in good agreement (<5%) with both models. The simulation with EMMS drag model predicted the pressure profiles more accurately than Wen-Yu/Ergun drag model. The profiles of particle volume fraction and axial velocity demonstrate that core-annulus flow pattern was captured by both models. But EM1VIS drag model was better in revealing the meso-scale structures at instantaneous particle concentration distribution. Moreover, the influence of particle size distribution on particle volume fraction and particle velocity profiles is also investigated with two drag models.
Keywords: CFB; Experimental; Cold flow; CPFD; Drag model; CIRCULATING FLUIDIZED-BED; PARTICLE-SIZE DISTRIBUTION; GAS-SOLID FLOWS; EMMS DRAG; 2-FLUID MODEL; HYDRODYNAMICS; COMBUSTION; VALIDATION; BIOMASS; COAL